Pengaruh Pupuk Organik Cair (Daun Gamal, Batang Pisang, Kulit Pisang) Sebagai Sumber NPK Terhadap Pertumbuhan Tanaman Selada (Lactuca sativa L.) - Novita Anggriani Nur; Zulzain Ilahude; Nurmi (Transbahasa, 2025)
This research aims to analyze the effect of liquid organic fertilizer (POC) made from gamal leaves, banana stems, and banana peels as a source of NPK on the growth of lettuce (Lactuca sativa L.) and determine the most effective POC dose. The research was conducted in Pulubala Village, Gorontalo City, from June to August 2023, using a Randomized Block Design (RBD) with 10 replications and 4 treatments: P0 (control, without POC), P1 (gamal leaf POC 120 ml + banana stem 70 ml + banana peel 100 ml), P2 (gamal leaf POC 70 ml + banana stem 100 ml + banana peel 120 ml), and P3 (gamal leaf POC 100 ml + banana stem 120 ml + banana peel 70 ml). Observed parameters included plant height, leaf count, stem diameter, and fresh weight. The results showed that POC application had a significant effect (α=5%) on plant height at 28, 35, and 42 days after planting (DAP), leaf count at 35 and 42 DAP, and fresh weight. However, it had no significant effect on stem diameter. Treatment P1 (gamal leaf 120 ml + banana stem 70 ml + banana peel 100 ml) yielded the best results in all significant parameters, with average plant height of 42.17 cm (42 DAP), leaf count of 14 leaves (42 DAP), and fresh weight of 37.77 g.